Trisindoline 5 Compound Inhibits Human Breast Cancer Stem Cell Formation by Downregulating the BCL-2 Gene Expression - Fatoni, Muhammad; Salsabila, Yofinta I; Nurhayati, Awik P.D.; Ghaissani, Shabrina Syifa; Santoso, Mardi; Martak, Fahimah (Stem Cell and Cancer Research (SCCR), 2022)
Background: Breast cancer cell's growth and survival are supported by breast cancer stem cells (bCSCs) mammosphere formation. bCSCs represent a subpopulation of undifferentiated cancer cells which associated with self-renewing abilities, tumor initiation, drug resistance, and metastasis. Overexpression of the B Cell Lymphoma 2 (BCL-2) family in many tumor cells contributes to apoptosis resistance. Trisindoline is an indole trimer alkaloid natural compound that provides a cytotoxic effect on cancer cells. A new modification of trisindoline has been synthesized into trisindoline 5 in 2021. Objective: This study purposed to investigate the effect of trisindoline 5 compounds against BCL-2 gene expression in bCSCs in vitro. Methods: The bCSCs MDA-MB-231 were divided into control and treatment groups which were further analyzed in gene expression using the qPCR Livak method. Results: Based on gene expression analysis, the results showed that trisindoline 5 may decrease the expression of BCL-2 in MDA-MB-231 cells. Conclusion: This study concludes that trisindoline 5 could downregulate the antiapoptotic BCL-2 gene expression in bCSCs in vitro.